The effect of water quality on the growth and yield of irrigated crops - Dikgwatlhe, Shadrack Batsile (University of the Free State, 2006)
Salinity is a major limitation and threat sustainable crop production in South Africa and elsewhere in the world. An intensive study by Du Preez et al. (2000) on the water quality of the lower Vaal River system using international salinity indicators were conducted and it was concluded that unacceptable damage to crops would be experienced if the salinity of the irrigation water continued to increase at the projected rates. Following that, intensive germination and glasshouse pot experiments were conducted based on the projected longterm salt accumulation on irrigated soils. Little or no quantitative information on the subject was available for South African conditions. This study was also part of a WRC project titled: The effect of irrigation water salinity on the growth and water use of selected crops. The objective of this study was to quantify the effect of different saline irrigation water levels (electrical conductivity, ECi ) on the germination, growth and yield of selected crops, viz. wheat (Triticum aestivum L. - SST 806.), maize (Zea mays L. - PNR 6335), peas (Pisum sativum L. - Solara) and beans (Phaseolus vulgaris L. - Teebus) at different growth stages. These crops were subjected to five different ECi levels (15 - control, 150, 300, 450, 600 for wheat and maize, and additionally 1200 mSm-1 for wheat, and 15 - control, 75, 150, 225, 300 mS m-1 for peas and beans). Three stages were used for each crop, viz. tillering, flag leaf and maturity (wheat), 2, 4 and 6 wae - weeks after emergence (maize) and 5 wae - five weeks after emergence, flowering and maturity (peas and beans). Various morphological indicators presented on a relative scale were measured to quantify the impact of ECi levels on both below and above ground growth. When subjecting the crops to the different ECi levels, the salt tolerance of these plants was taken into consideration. These crops were affected at varying degrees, depending on the salt sensitivity of the crop involved. Interesting results were obtained for all the crops and based on the findings the study agreed well with the international accepted salinity classification system where wheat is classified as moderately tolerant and peas and beans as sensitive. Maize proved to be sensitive in this study, but it has to be noted that it was only at a very early growth stage. The water use of the pot experiment plants was found to be very high and this was attributed to the smaller volume of soil relative to the canopy. All plant growth indicators proved to be negatively affected over the selected ECi range. The reduction in growth for all crops followed a similar trend with increasing ECi levels. The EC of the saturation soil extract (ECe) was also measured in order to determine the rate of soil salinisation and was found to be 2 to 3 times that of ECi. The study also compared the responses of these crops by using primary growth indicators (leaf area, root mass, biomass and seed yield) and also attempted to determine the salt tolerance values using the regression coefficients. Therefore, all the objectives set for the study were achieved. The effect of salinity on a variety of other crops under South African conditions should be thoroughly and comprehensively investigated in future.

Verbrakking beperk en bedreig volhoubare gewasproduksie in Suid-Afrika en ander wêrelddele. ’n Intensiewe studie is deur Du Preez et al. (2000) op die waterkwaliteit van die laer Vaalrivier sisteem uitgevoer deur gebruik te maak van internasionale verbrakkings indikatore en die gevolgtrekking is gemaak dat gewasproduksie tot onaanvaarbare vlakke banadeel sou word indien die tempo van soutakkumalasie in besproeiingswater gehandhaaf word. Na aanleiding van dié studie is intensiewe ontkiemings en glashuispotproewe, gebasseer op die voorgenome langtermyn soutakkumulasie op besproeiingsgronde, uitgevoer. Weinig kwantitatiewe inligting oor die onderwerp is vir Suid-Afrikaanse toestande beskikbaar. Hierdie studie het ook deel gevorm van ’n WNK-projek, getiteld: The effect of irrigation water salinity on the growth and water use of selected crops. Die doel van die studie was om die invloed van besproeiingswater met verskillende soutkonsentrasies (elektriese geleiding, ECi) op die ontkieming, groei en opbrengs van geselekteerde gewasse, viz. koring (Triticum aestivum L. - SST 806.), mielies (Zea mays L. - PNR 6335), droë erte (Pisum sativum L. - Solara) en droëbone (Phaseolus vulgaris L. - Teebus) by verskillende groeistadiums, te kwantifiseer. Die gewasse is onderwerp aan vyf verskillende ECi vlakke (15 - kontrole, 150, 300, 450, 600 vir koring en mielies, met ’n addisionele 1200 mSm-1 vir koring en 15 - kontrole, 75, 150, 225, 300 mS m-1 vir erte en boontjies). Drie groeistadiums is vir elke gewas gebruik, viz. stoel, vlagblaar en volwassenheid (koring), 2, 4 en 6 wae – weke na opkoms (mielies) en 5 wae - vyf weke na opkoms, blom em volwassenheid (erte en boontjies). Verskeie morfologiese parameters/indikatore, op ’n relatiewe skaal voorgestel, is gemeet om die invloed van ECi vlakke op beide die ondergrondse en bogrondse groei te kwantifiseer. Die gewasse se toleransie is ook in ag geneem tydens onderwerping aan die verskillende ECi vlakke. Die mate waartoe die gewasse beïnvloed is, is bepaal deur die gewasse se gevoeligheid. Interessante resultate is verkry vir al die gewasse en op grond van hierdie resultate het die studie goed vergelyk met bevindings van die internasionaal aanvaarde sout gevoeligheids klassifikasie sisteem waar koring as matig tolerant en erte en boontjies as sensitief geklassifiseer word. Mielies was redelik sensitief tydens die studie, maar dit is belangrik om doorop te let dat slegs op’n vroeë vegetatiewe stadium was. Die waterverbruik van die potproefplante was besonder hoog en is toegeskryf aan die klein volume grond in verhouding tot die totale blaaroppervlakte. Alle plantindikatore is negatief beïnvloed oor die geselekteerde ECi reeks. Die afname in groei van al die gewasse het soortgelyke tendense met ’n toename in ECi getoon. Die EC van die versadigde grondekstrak (ECe) is ook gemeet in ’n poging om die tempo waartoe sout in die grond akkumuleer te bepaal en daar is gevind dat die ECe van die grond 2 tot 3 keer die van ECi was. Tydens die studie is die verskillende gewasse se gewasreaksie ook vergelyk deur van geselekteerde plantindikatore (blaaroppervlakte, wortelmassa, biomassa en saad opbrengs) gebruik te maak. Daar is ook gepoog om die souttoleransie van die gewasse te bepaal deur van regresssie koëffisiente gebruik te maak. Daar is dus aan al die doelstellings van die studie voldoen. In die toekoms moet daar op die invloed van verbrakking op ’n verkeidenheid ander gewasse onder Suid-Afrikaanse toestande gekonsentreer en in diepte ondersoek word.
Dissertation (M.Sc.Agric. (Soil, Crop and Climate Sciences))--University of the Free State, 2006
Keywords: Germination; Growth; Yield; Salinity; Water quality; Irrigation; Wheat; Maize; Peas; Beans; Irrigation water -- Quality; Soils, Salts in -- South Africa; Crops -- Effect of salts on -- South Africa